Descriptive Analysis Of Context Evaluation Instrument For Technical Oral Presentation Skills Evaluation: A Case Study In English Technical Communication Course - Abdullah Adnan, Mohamed; Adelina, Asmawi; M. R., Abdul Hamid; Zainol, Mustafa (2015)
This paper reports a pilot study of Context Evaluation using a self-developed questionnaire distributed among engineering undergraduates at a university under study. The study aims to validate the self-developed questionnaires used in the Context evaluation, a component in the CIPP Model. The Context evaluation assesses background information for needs, assets, problems and opportunities relevant to beneficiaries of the study in a defined environment. Through the questionnaire, background information for the assessment of needs, assets and problems related to the engineering undergraduates' perceptions on the teaching and learning of technical oral presentation skills was collected and analysed. The questionnaire was developed using 5-points Likert scale to measure the constructs under study. They were distributed to 100 respondents with 79 returned. The respondents consisted of engineering undergraduates studied at various faculties at one technical university in Malaysia. The descriptive analysis of data for each item which makes up the construct for Context evaluation is found to be high. This implied that engineering undergraduates showed high interest in teaching and learning of technical oral presentation skills, thus their needs are met. Also, they agreed that assets and facilities are conducive to their learning. In conclusion, the context evaluation involving needs and assets factors are both considerably important; their needs are met and the assets and facilities do support their technical oral presentation skills learning experience.